2016
DOI: 10.1016/j.biochi.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in ribosomal protein L19 that decrease the fidelity of translation

Abstract: Ribosomal protein L19 is an essential ribosomal protein and is a component of bridge B8, one of the protein-RNA bridges linking the large and small ribosomal subunits. Bridge B8 also contributes to the accuracy of translation by affecting GTPase activation by ribosome-bound aminoacyl tRNA-EF-Tu•GTP ternary complexes. Previous work has identified a limited number of accuracy-altering alterations in protein L19 of Salmonella enterica and Thermus thermophilus. Here, we have targeted the Escherichia coli rplS gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The phosphorylation of ribosomal proteins can reduce up to 50% of their activity ( Mikulík et al, 2001 ), although it seems that phosphorylated L19 is the active form of the protein that contribute to the assembly and decoding processes ( Soung et al, 2009 ). Moreover, a mutagenic study of the rplS gene in E. coli revealed that, despite the restraint in translation, the defective mutants did not exhibit problems in 30S–50S association or cell growth ( VanNice et al, 2016 ). There is no record of L19 protein as a drug target in the DrugBank database.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of ribosomal proteins can reduce up to 50% of their activity ( Mikulík et al, 2001 ), although it seems that phosphorylated L19 is the active form of the protein that contribute to the assembly and decoding processes ( Soung et al, 2009 ). Moreover, a mutagenic study of the rplS gene in E. coli revealed that, despite the restraint in translation, the defective mutants did not exhibit problems in 30S–50S association or cell growth ( VanNice et al, 2016 ). There is no record of L19 protein as a drug target in the DrugBank database.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of genes that formed GIs with ITT1 and RPS1A are large ribosomal subunit protein 19A ( RPL19A ) and general control non-derepressible ( GCN3 ), respectively. Rpl19p is a conserved large ribosomal subunit protein involved in ribosomal intersubunit bridging and its alteration is connected to the fidelity of translation [ 54 ], [ 55 ]. On the other hand, GCN3 is the alpha subunit of translation initiation factor 2B (eIF2B), which is involved in guanine-nucleotide exchange for eIF2.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of genes that formed GIs with ITT1 and RPS1A are large ribosomal subunit protein 19A (RPL19A) and general control non-derepressible (GCN3), respectively. Rpl19p is a conserved large ribosomal subunit protein involved in ribosomal intersubunit bridging and its alteration is connected to the fidelity of translation [54], [55]. On the .…”
Section: Genetic Interaction Analysis Further Connects the Activity Omentioning
confidence: 99%